Phospholipid transfer protein and alpha-1 antitrypsin regulate Hck kinase activity during neutrophil degranulation. Issue 1 (December 2018) - Ochieng, Pius; Nath, Sridesh; Macarulay, Reane; Eden, Edward; Dabo, Abdoulaye; Campos, Michael; Jiang, Xian-Cheng; Foronjy, Robert; Geraghty, Patrick
Abstract Excessive neutrophil degranulation is a common feature of many inflammatory disorders, including alpha-1 antitrypsin (AAT) deficiency. Our group has demonstrated that phospholipid transfer protein (PLTP) prevents neutrophil degranulation but serine proteases, which AAT inhibits, cleave PLTP in diseased airways. We propose to identify if airway PLTP activity can be restored by AAT augmentation therapy and how PLTP subdues degranulation of neutrophils in AAT deficient subjects. Airway PLTP activity was lower in AAT deficient patients but elevated in the airways of patients on augmentation therapy. Functional AAT protein (from PiMM homozygotes) prevented PLTP cleavage unlike its mutated ZZ variant (PiZZ). PLTP lowered leukotriene B4 induced degranulation of primary, secondary and tertiary granules from neutrophils from both groups (n = 14/group). Neutrophils isolated fromPltp knockout mice have enhance neutrophil degranulation. Both AAT and PLTP reduced neutrophil degranulation and superoxide production, possibly though their inhibition of the Src tyrosine kinase, Hck. Src kinase inhibitors saracatinib and dasatinib reduced neutrophil degranulation and superoxide production. Therefore, AAT protects PLTP from proteolytic cleavage and both AAT and PLTP mediate degranulation, possibly via Hck tyrosine kinase inhibition. Deficiency of AAT could contribute to reduced lung PLTP activity and elevated neutrophil signaling associated with lung disease.